Effects of Chemical Solution Temperature on the Bulk Etch Rate of the Detector CR-39 - Sa'eed Hassan Sa'eed Al-Nia’emi (Jordan Journal of Physics, 2025)
The effects of chemical etchant temperatures on the bulk etch rate VB of CR-39 SNTDs were investigated. The bulk etch rate is determined through direct measurement of "length-diameter Le-D" of alpha-particles track in the detector. Alpha-particles irradiations were made with energy of 2.5MeV under normal incidence radioactive source 241Am of an activity of 1 µCi. The detector is etched by an aqueous solution of NaOH/water with 6.25 normality N in the temperature range (55,60, 65, 70) ±1 oC. The lengths and diameters of alpha-particles tracks are directly measured from the tracks images obtained from the irradiated detector. It was found that the bulk etch rate is exponentially increasing with the temperature of the solution and its values ranged between (1.1022- 1.424) µm.h-1 in the above temperature range. Keywords: CR-39; Track etch; Alpha particle; Nuclear track detector.